MIKROBA PENCEMAR DI PERAIRAN TELUK JAKARTA - Nur Fitriah Afianti; Lies Indah Sutiknowati (Pusat Penelitian Oseanografi LIPI, 2017)
MICROBE CONTAMINANT IN JAKARTA BAY WATERS. High anthropogenic activity in Jakarta Bay is believed to contribute a fairly high contamination as evidenced by microbial contaminants such as Coliform and Escherichia coli. The high density of Coliform and E. coli as indicators of domestic contamination in Jakarta Bay as a result of an increase in the resident numbers who bring the flow of water to the springhead of the Jakarta Bay. It can be said that the polluted waters of Jakarta Bay and marine biota should be cultivated in this area as green shell should not consumed, because it can infect and cause gastrointestinal diseases. For that purpose, a research of microbial pollutants was conducted in Jakarta Bay in July 2015, and the results showed a very high density, especially in the West.